A Low-throughput Wavelet-based Steganography Audio Scheme - Carrión, P.; Oliveira, H. M. de; Souza, R. M. Campello de (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2008: Companion Proceedings of the 8th Brazilian Symposium on Information and Computational Systems SecurityDO - 10.5753/sbseg_estendido.2008.20906, 2008)
This article does not have an abstract.